Gender Perspective in the Studies of War - T. V. Skorospelova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Feminist studies, first introduced in international relations theory back in the Cold War, established themselves as an independent research field in 1990s. From the onset, feminist studies have been focused on the key concepts and notions of the IR theory, such as ‘state’, ‘power’, ‘security’, and ‘war’. It is exactly the role of gender perspective in the studies of war in the modern context which is the central issue of this paper. The first section examines feminist views on traditional gender roles attributed to women at war: the image of mother, the keeper of the hearth, and the image of victim. The author emphasizes that behind these roles lays a much broader set of issues, which involves legitimization of a particular structure of power relations in society in general. The second section focuses on perceptions of new gender roles of women at war, which include the images of a woman as a soldier and a terrorist, both in the academic discourse and in the media. The author underlines a paradox in this regard: whereas the practice of inter- and intrastate conflicts has already resulted in the entrenchment of the new female gender roles, gender stereotypes continue to dominate both the IR theory and mass consciousness. The author concludes that the issues of war and security will continue to play a crucial role in the development of feminist studies in the IR theory and outlines several promising directions for further research in this area.